Acute respiratory illness in the community: effect of family composition, smoking, and chronic symptoms. Issue 2 (June 1977) - Monto, A S; Ross, H
Abstract : Respiratory illness and infection was studied in the community of Tecumseh, Michigan, USA, during a six-year period. Acute illness was ascertained by making weekly telephone calls, and prevalent agents were identified by microbial isolation. Infection rates were determined serologically using blood specimens collected routinely at six monthly intervals from those reported to be ill. Illness rates were higher in the youngest children of families up to the age of three years than for the oldest children of the same ages. Above the age of three, the pattern was reversed. Among the adults, rates of illness were shown to relate not only to the presence, but also to the age of children in the home. Throughout this comparison, women were more likely to be ill than men in the same groups. Smoking in itself was not related to increased acute respiratory illnesses, but persons with symptoms of chronic bronchitis were found to have higher illness rates independently of whether they smoked.